Online Marketing Communication Model of R80 Aircraft Fundraising (Netnographic Study for E-Commerce and Facebook @Kitabisadotcom) - Ayu Nurfitri Andini; Nani Nurani Muksin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Kitabisa.com websites are focuses on social movements, with the market being foundations, and individuals who need social support/assistance. Kitabisa.com provides online donation platforms and technology for individuals, communities, organizations, institutions, and companies. This study aims to understand the online marketing communication process (messages, endorsements, media, target/audience, and feedback), analyze the online media used by the endorser group (fundraisers, donors, and Kitabisa.com page managers) as marketing communications to raise donations for R80 aircraft, knowing the supporting and inhibiting factors of online marketing communication for raising donations for the R80 aircraft, and finding an online marketing communication model for raising donations for the R80 aircraft. This research uses a qualitative approach with a netnography methodology. It was found that the online marketing communication process applied in raising donations for R80 aircraft through Kitabisa.com is based on online marketing communications that provide feedback channels for donors and influencers. In addition, the social media Facebook account @kitabisadotcom also plays a major role in maximizing User Generate Content (UGC) from influencer accounts, increasing reach through sharing activities (To Share), generating collaboration (To Co-operate) and increasing interaction. Some of the supporting factors include the character of Professor BJ Habibie as the architect of the R80 aircraft and also known as the Father of Indonesian Technology and the 3rd President of the Republic of Indonesia, the character of the influencers who support the donation-raising campaign, and the concept of storytelling plays a big role in mobilizing people to donate. This research was found the uniqueness online marketing communication models which has a new stage effect that occurs on the audience that they are feeling proud and buying merchandise and doing as a fundraiser.